Stedsnavn i Tirol: endonymiprinsippets utfordringer i møtet med språklig og toponymisk mangfold - Sandvik, Hanno (NAMN OG NEMNE, 2023)
Toponyms of Tyrol – how to apply the endonymic principle in a highly diverse namescapeTyrol has an extraordinary diversity of toponyms, which is due to the various languages that have been and are spoken in this mountainous area. After presenting the «namescape» of Tyrol (North Tyrol, East Tyrol, South Tyrol and Trentino), the article addresses the challenges that the toponymy of Tyrol poses for the official Norwegian spelling norm and identifies two problems. First, the spelling of the landscape itself («Tyrol») is incompatible with the endonymic principle (which demands «Tirol»). Second, most toponyms of South Tyrol are currently normalised in their Italian forms. However, the endonymic principle suggests that the norm should allow all forms that are locally well-established. A coherent alternative to the current Norwegian spelling norm is suggested. Further recommendations are given regarding the Norwegian spelling of Tyrolean toponyms that are not covered by the official norm.